Sağlık çalışanlarının cinsiyetlerine göre cinsel mitlere yönelik algılarının incelenmesi - Demir Erdinç, Ecem (My University, 2025)
Amaç: Bu çalışmada, sağlık çalışanlarının cinsiyetlerine göre cinsel mitlere yönelik algılarının incelenmesi amaçlandı. Gereç ve Yöntem: Tanımlatıcı tipte ve ilişki arayıcı olarak tasarlanan bu çalışma, Aralık 2023- Haziran 2024 tarihleri arasında gerçekleştirildi. Örneklem büyüklüğü hesaplamasında “Evreni Bilinen Örneklem Formülünden yararlanıldı ve incelenen olayın görülüş sıklığı için %95 değeri referans olarak alındı. Evren olarak Türkiye’de 2023 yılında çalışan sağlık profesyoneli sayısı (1.420.000) baz alındı. Örnekleme yöntemi olarak olasılıksız örnekleme yöntemlerinden kartopu örneklemesi kullanıldı ve toplam 250 sağlık çalışanına ulaştıktan sonra çalışma sonlandırıldı. Veriler Kişisel Bilgi Formu ve Cinsel Mitler Ölçeği (CMÖ) ile toplanıldı. Verilerin analizi Statistical Package for the Social Sciences (SPSS) versiyon27 de yapıldı. Bulgular: Çalışmaya katılan sağlık çalışanlarında yaş aralığı 20-61 arasında olup ortalaması 34,98±8,5 ti, toplamda %63,6’sı kadındı ve %67,2’si evliydi. Meslek olarak %33,2 ile hemşireler ilk sıradaydı. Büyüdükleri aile yapısını %46,8’i “muhafazakâr ve baskıcı- tutucu” olarak tanımlamıştı ve kadın erkek açısından oranlar benzerdi (p>0,05). Sağlık çalışanlarının %68,8’i “cinsellikle ilgili aile içinde konuşulmadığını, yasak, ayıp olarak karşılandığını rapor etti. Cinsellikle ilgili içinde yaşadığı toplumsal, kültürel normlar ve tabuların kendisini etkileme düzeyine 10 üzerinden ortalama 5,19±2,31 puan, kültürel normlar ve tabuların cinsellikle ilgili sağlık hizmeti vermesini etkileme/ etkileyeceğini düşünme düzeyine de ortalama 4,60±2,50 puan vermişlerdi. Cinsel Mitler Ölçeği (CMÖ) total puan ortalaması 64,00±25,00 dı ve CMÖ cinsel yönelim alt boyutu hariç diğer tüm alt boyut ve totalde erkek sağlık çalışanlarının puanları kadınlara göre yüksekti (p<0,05-0,001). CMÖ totalde aile yapıları muhafazakâr ve baskıcı- tutucu olanların puanları daha yüksekti (p<0,001). Yaş arttıkça CMÖ puanlarının arttığı, CMÖ puanı arttıkça cinsellikle ilgili içinde yaşadığı toplumsal, kültürel normlar ve tabuların sağlık çalışanlarını etkileme düzeyinin arttığı belirlendi (p<0,05-0,001). Sonuç; Sağlık çalışanlarında toplumuzdaki cinsel mitlere ilişkin inancın orta düzeyde olduğu, erkeklerde, ileri yaşlarda, büyüdüğü aile yapısı muhafazakâr ve baskıcı- tutucu olanlarda bu düzeyin arttığı söylenebilir.

Objective: This study aimed to examine the perceptions of healthcare professionals regarding sexual myths according to their gender. Materials and Methods: This study, designed as a descriptive and relationship-seeking study, was conducted between December 2023 and June 2024. The “Sampling Formula with a Known Universe” was used in the sample size calculation and the %95 value was taken as the reference for the frequency of the event under study. The number of healthcare professionals working in Turkey in 2023 (1,420,000) was taken as the basis for the universe. Snowball sampling, one of the non-probability sampling methods, was used as the sampling method and the study was terminated after reaching a total of 250 healthcare professionals. Data were collected with the Personal Information Form and the Sexual Myths Scale (SMS). Data analysis was done in the Statistical Package for the Social Sciences (SPSS) version 27. Results: The age range of the healthcare workers participating in the study was between 20 and 61, with an average of 34,98±8,5, %63,6 were women in total and %67,2 were married. Nurses were in the first place with %33,2 as a profession. %46,8 described the family structure they grew up in as “conservative and oppressive-conservative” and the rates were similar for women and men (p>0,05). %68,8 of healthcare workers reported that “sexuality is not discussed within the family and is considered forbidden and shameful. They gave an average score of 5,19±2,31 out of 10 for the level of influence of the social and cultural norms and taboos they live in regarding sexuality, and an average score of 4,60±2,50 for the level of influence/ thinking that cultural norms and taboos will influence providing healthcare services regarding sexuality. The total score average of the Sexual Myths Scale (SMS) was 64,00±25,00 and the scores of male healthcare workers were higher than females in all sub-dimensions and in total, except for the sexual orientation sub-dimension of the SMS (p<0,05-0,001). The scores of those with conservative and oppressive-conservative family structures were higher in the SMS total (p<0,001). It was determined that the SMS scores increased as age increased, and that the level of influence of the social and cultural norms and taboos they live in regarding sexuality on healthcare workers increased as the SMS score increased. (p<0,05-0,001). Conclusion: It can be said that the belief in sexual myths in our society is at a moderate level among healthcare professionals, and this level increases in men, older people, and those whose family structure was conservative and oppressive.
Investigation of healthcare workers' perceptions of sexual myths according to their gender
Keywords: cinsel mitler; cinsellik; cinsiyet; Doğum hemşireliği; gender; Healthcare professionals; Obstetric nursing; Sağlık çalışanları; sexual myths; sexuality